2023
DOI: 10.1002/dro2.55
|View full text |Cite
|
Sign up to set email alerts
|

From capture to transport: A review of engineered surfaces for fog collection

Abstract: Collecting microscale water droplets suspended in the wind, that is, fog, using permeable surfaces is a promising solution to the worldwide problem of water scarcity and is of great interest to industries, such as mist elimination and recapturing water in cooling towers. In the past few decades, this topic has attracted a drastically increasing number of researchers across a wide range of subjects. However, many aspects remain unclear, such as the definition and process of fog collection, fog collection determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 169 publications
0
9
0
Order By: Relevance
“…23−25 Shi et al 26 developed fog harps, which are arrays of vertical fibers and give enhanced fogharvesting performance due to the absence of cross fibers, which otherwise hinder droplet motion leading to pinning of droplets and clogging of mesh pores. As pointed out in a recent review by Jiang et al, 27 fog harvesting is distinct from dew harvesting. In fog harvesting, condensed liquid water droplets suspended in air are captured by inertial impact, while in dew condensation, droplets grow by vapor-to-liquid phase change on a surface maintained at a temperature lower than the saturation temperature of the vapor at the operating pressure.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…23−25 Shi et al 26 developed fog harps, which are arrays of vertical fibers and give enhanced fogharvesting performance due to the absence of cross fibers, which otherwise hinder droplet motion leading to pinning of droplets and clogging of mesh pores. As pointed out in a recent review by Jiang et al, 27 fog harvesting is distinct from dew harvesting. In fog harvesting, condensed liquid water droplets suspended in air are captured by inertial impact, while in dew condensation, droplets grow by vapor-to-liquid phase change on a surface maintained at a temperature lower than the saturation temperature of the vapor at the operating pressure.…”
Section: ■ Introductionmentioning
confidence: 96%
“…They include desert beetle-inspired surfaces with heterogeneous wettability, , Janus membranes with front-to-back wettability gradient for fast water removal, utilizing Laplace pressure gradient caused by asymmetric curvatures on conical surfaces, , or incorporating special topological features which enable unidirectional motions of droplets. Shi et al developed fog harps, which are arrays of vertical fibers and give enhanced fog-harvesting performance due to the absence of cross fibers, which otherwise hinder droplet motion leading to pinning of droplets and clogging of mesh pores. As pointed out in a recent review by Jiang et al, fog harvesting is distinct from dew harvesting. In fog harvesting, condensed liquid water droplets suspended in air are captured by inertial impact, while in dew condensation, droplets grow by vapor-to-liquid phase change on a surface maintained at a temperature lower than the saturation temperature of the vapor at the operating pressure.…”
Section: Introductionmentioning
confidence: 98%
“…21 Although the superhydrophilic single wedge-shaped pattern successfully demonstrated the transportation capability in the SDWT, the Laplace pressure difference of the water droplet significantly decreased due to the large end size, which meant that the single wedge-shaped pattern was not suitable for long-distance water transportation. 22–25 To overcome this limitation, a superhydrophilic serial wedge-shaped pattern (SSWP), where the pattern consisted of several single wedge-shaped patterns connected in a head-to-tail arrangement, was proposed in our previous study, which was facilitated to decrease the fluid loss, resulting in the increase of the transportation distance. 26,27 However, researchers found that once the water droplet moved to the junction of the SSWP, the droplet would encounter the resistance force from the pinning, resulting in the decrease of the water transportation velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet directional transport is of scientific importance and has practical applications in many fields, such as fusion and separation of droplets in microfluidic chips, rapid growth and transport of droplets and fog in collection systems, , selective transport of droplets with different surface tensions in oil–water separation devices, , removal of droplets in deicing and antifrosting design, , and so on. In nature, multifarious organisms use their special structures to control liquid movement, such as the conical thorns of cactus, the periodic thorns of spider silk, the ratchet scales of butterfly wings, , the three-dimensional ratchets of araucaria leaf, etc.…”
Section: Introductionmentioning
confidence: 99%